A business plan for a startup of an international school targeting middle income group in Malaysia - Goh, Moi Huee (2018)
PRIME International School, PRIS in short is an international private school that will be located in the suggested area, Kepong as it is one of the high density areas with 360,000 population in that area. It has only one international school which is targeting to a higher income group segment compared with PRIS. There are other neighbouring area such as Gombak, Selayang, Sentul and Batu Caves can be the potential targeted area as well. PRIS will be running the British syllabus which is one of the world’s popular and widely acceptable syllabus. There will be Nursery (3 years), Primary (6 Years) and Secondary (3 years) up till form 3 offered by PRIS at the moment due to the high set up cost.